2007
DOI: 10.1038/sj.emboj.7601884
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent requirement of AKAP150-anchored PKA and GluR2-lacking AMPA receptors in LTP

Abstract: Association of PKA with the AMPA receptor GluR1 subunit via the A kinase anchor protein AKAP150 is crucial for GluR1 phosphorylation. Mutating the AKAP150 gene to specifically prevent PKA binding reduced PKA within postsynaptic densities (>70%). It abolished hippocampal LTP in 7–12 but not 4‐week‐old mice. Inhibitors of PKA and of GluR2‐lacking AMPA receptors blocked single tetanus LTP in hippocampal slices of 8 but not 4‐week‐old WT mice. Inhibitors of GluR2‐lacking AMPA receptors also prevented LTP in 2 but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
251
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(281 citation statements)
references
References 81 publications
24
251
5
Order By: Relevance
“…Recent studies showed that LTP induces a rapid but transient increase in synaptic expression of GluR2-lacking Ca 2ϩ -permeable AMPARs in 10 to 12-day-old mice. Although these receptors are subsequently replaced by GluR2-containing AMPARs, their transient expression in the synapse increases Ca 2ϩ permeability, and may contribute to the stabilization of LTP (Plant et al, 2006;Lu et al, 2007b). At later developmental stages GluR2-lacking AMPARs are no longer required for the early phase of LTP (Lu et al, 2007b), which may explain the discrepancies found in the literature concerning this issue (Adesnik and Nicoll, 2007;Gray et al, 2007).…”
Section: Role Of Ampars In Ltpcontrasting
confidence: 50%
See 1 more Smart Citation
“…Recent studies showed that LTP induces a rapid but transient increase in synaptic expression of GluR2-lacking Ca 2ϩ -permeable AMPARs in 10 to 12-day-old mice. Although these receptors are subsequently replaced by GluR2-containing AMPARs, their transient expression in the synapse increases Ca 2ϩ permeability, and may contribute to the stabilization of LTP (Plant et al, 2006;Lu et al, 2007b). At later developmental stages GluR2-lacking AMPARs are no longer required for the early phase of LTP (Lu et al, 2007b), which may explain the discrepancies found in the literature concerning this issue (Adesnik and Nicoll, 2007;Gray et al, 2007).…”
Section: Role Of Ampars In Ltpcontrasting
confidence: 50%
“…Although these receptors are subsequently replaced by GluR2-containing AMPARs, their transient expression in the synapse increases Ca 2ϩ permeability, and may contribute to the stabilization of LTP (Plant et al, 2006;Lu et al, 2007b). At later developmental stages GluR2-lacking AMPARs are no longer required for the early phase of LTP (Lu et al, 2007b), which may explain the discrepancies found in the literature concerning this issue (Adesnik and Nicoll, 2007;Gray et al, 2007). Under resting conditions AMPARs are recycled in a constitutive manner between synapses and intracellular membrane compartments, where they are sorted for degradation or for reinsertion at synapses (Ehlers, 2000;Passafaro et al, 2001) (see above).…”
Section: Role Of Ampars In Ltpmentioning
confidence: 99%
“…16, but see ref. 15), and does not require exocytosis (43). Further testing is required to determine whether different forms of LTP coexist and, if so, under what conditions one form or the other is selectively induced, and whether the expression is synapse-specific given the known heterogeneity of synaptic compositions (44).…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence indicates that the molecular composition of synaptic AMPA receptors is altered following activity-dependent changes in synaptic strength ( [31][32][33]; but also note [34,35]). Similarly, alterations in AMPA receptor trafficking are implicated in leptin-induced LTP as an increase in AMPA receptor rectification accompanied the leptin-driven increase in synaptic efficacy.…”
Section: Leptin-induced Long-term Potentiation At Adult Hippocampal Cmentioning
confidence: 99%